Aspirin Prophylaxis During Pregnancy: A Systematic Review and Meta-Analysis - Choi, Yeo Jin; Shin, Sooyoung (American Journal of Preventive Medicine, 2021)
Context: Low-dose aspirin is used for pre-eclampsia prophylaxis during pregnancy, but a study that comprehensively investigates both maternal and perinatal outcomes from aspirin administration utilizing stratification methods is lacking. The aim of this study is to comprehensively investigate the maternal and neonatal outcomes related to aspirin prophylaxis during pregnancy in relation to dose and therapy initiation by utilizing a stratification method. Evidence acquisition: Placebo-controlled randomized trials investigating the effect of low-dose aspirin on maternal or perinatal outcomes with sufficient raw data and published in English from inception to August 2020 were searched for from PubMed, Embase, Cochrane Library, and Google Scholar in accordance with PRISMA guidelines. Review articles, editorials, case reports, conference abstracts, and nonplacebo-controlled studies were excluded. Evidence synthesis: A total of 35 placebo-controlled randomized trials with 46,568 pregnant women were included in this meta-analysis. Aspirin prophylaxis substantially lowered the risk of pre-eclampsia, preterm birth, perinatal mortality, and intrauterine growth retardation without elevated bleeding risks. Low-dose aspirin considerably enhanced neonatal birth weight but did not decrease the risk of gestational hypertension. The subgroup analysis revealed substantially reduced pre-eclampsia risk and enhanced birth weight and gestational age at delivery in women who initiated aspirin before 20 weeks of gestation (RR=0.76, 95% CI=0.64, 0.90, p=0.001). However, the effect of aspirin dose on pregnancy outcomes was insignificant and requires further evaluation. Conclusions: Initiation of low-dose aspirin administration before 20 weeks of gestation considerably decreases the incidence of pre-eclampsia and related neonatal outcomes without increasing bleeding risk.
Keywords: Aspirin; Female; Gestational Age; Humans; Infant, Newborn; Pre-Eclampsia; Pregnancy; Pregnancy Outcome; Premature Birth